Derivations of second type of algebra of second class filiform Leibniz algebras of dimension derivation (n+2) - Ahmad, AL-Nashri AL-hossain (International Journal of Advanced Mathematical Sciences, 2017)
In this article, the derivations of second type of algebra from the second class filiform Leibniz algebras of dimension derivation (n+2) is discussed. From the description of the derivations. It is found that the basis of the space Der(Ln(b)) of the algebra.